Examining the human infectious reservoir for Plasmodium falciparum malaria in areas of differing transmission intensity - Bronner P. Gonçalves; Melissa C. Kapulu; Patrick Sawa; Wamdaogo M. Guelbéogo; Alfred B. Tiono; Lynn Grignard; Will Stone; Joel Hellewell; Kjerstin Lanke; Guido J. H. Bastiaens; John Bradley; Issa Nébié; et al. (Nature Communications, 2017)
Heterogeneity in the transmission potential of individual hosts is an important feature of malaria. Here, the authors perform a multi-regional study of the human infectious reservoir in malaria-endemic regions of Burkina Faso and Kenya.